Decoration on Cubane with an Awareness of Chirality: Development of Substituted Cubane Syntheses - Takebe, Hiyori; Matsubara, Seijiro (Synthesis, 2023)
Nearly 60 years have passed since Professor Eaton’s practical synthesis of cubane, and research using it as a unique molecular scaffold has since gained momentum. Since the early synthesis of polynitrocubane, it has been shown that up to eight substituents can be covalently assembled into a confined space. The arrangement of substituents on cubane has paved the way for the creation of unique asymmetric molecules. To put it another way, chirality is manifested by selectively introducing three or more diverse types of substituents at specific sites. Recently, there has also been a report on the synthesis of perfluorocubane, a molecule with intriguing electronic properties.1 Introduction2 General Information3 Functionalization of Cubane4 Preparation of Polysubstituted Cubanes5 Conclusion
Keywords: cubane; HAT; DoM; chirality; cuneane